2021
DOI: 10.3389/fonc.2020.591430
|View full text |Cite
|
Sign up to set email alerts
|

Potential Clinical Significance of Overall Targeting Accuracy and Motion Management in the Treatment of Tumors That Move With Respiration: Lessons Learnt From a Quarter Century of Stereotactic Body Radiotherapy From Dose Response Models

Abstract: ObjectiveTo determine the long-term normal tissue complication probability with stereotactic body radiation therapy (SBRT) treatments for targets that move with respiration and its relation with the type of respiratory motion management (tracking vs. compression or gating).MethodsA PubMed search was performed for identifying literature regarding dose, volume, fractionation, and toxicity (grade 3 or higher) for SBRT treatments for tumors which move with respiration. From the identified papers logistic or probit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…All TT-users with C-arm linacs indicated they had participated in TROG trials using the KIM software. The lack of commercial solutions for conventional linacs is clearly still a major barrier to implementing TT in the clinic outside of the research setting, despite mounting evidence showing its benefit and feasibility [39] , [40] , [41] . Currently in ANZ, facilities who participate in KIM trials for TT undergo a credentialing process for this software, but it does not involve dosimetric measurements [35] .…”
Section: Discussionmentioning
confidence: 99%
“…All TT-users with C-arm linacs indicated they had participated in TROG trials using the KIM software. The lack of commercial solutions for conventional linacs is clearly still a major barrier to implementing TT in the clinic outside of the research setting, despite mounting evidence showing its benefit and feasibility [39] , [40] , [41] . Currently in ANZ, facilities who participate in KIM trials for TT undergo a credentialing process for this software, but it does not involve dosimetric measurements [35] .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there are more than 400 instances of "radiation AND 'deep inspiration breath hold'." Since Synchrony with breathhold scans has achieved remarkably good results, to be fair, it is important to ensure that an equitable number of publications of this technique is also permitted [5]. Accuray recommends normal exhale and normal inhale breathhold scans for Synchrony motion tracking, but since not all users employ that technique, it is important for researchers to specify which CT scan technique was used when reporting their results; these treatment variables are needed to enable QUANTEC and HyTEC style initiatives [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…It can usually be confirmed that deformation of the tumor in the region of the fiducials is less than a millimeter since many tumors have been measured to deform less than a millimeter during treatment [4]. The breathhold technique is recommended by the manufacturer of the Synchrony system and excellent outcomes have been achieved with this technique [5]; nevertheless, some Synchrony users are trying four-dimensional CT (4DCT) because of its widespread usage throughout the field. This study is not intended to prove superiority of either one, but rather just to explain the methodology of the breathhold technique and present results in a phantom and in a few patients.…”
Section: Introductionmentioning
confidence: 99%
“…This can affect machine learning auto segmentation accuracy [ 2 ] and restrict potential use cases for high dose rate radiotherapy where the target and organs at risk (OAR) undergo complex motion due to both cardiac deformation and respiration. Poor motion compensation combined with steep dose gradients can increase the risk of exceeding dose constraints in OARs, particularly where critical structures lie close to the target [ 3 8 ]. An example for cancer radiotherapy is the treatment of central lung or esophageal tumors located within close proximity to the heart [ 9 15 ].…”
Section: Introductionmentioning
confidence: 99%